Does mycorrhizal inoculation improve plant survival, aggregate stability, and fine root development on a coarse‐grained soil in an alpine eco‐engineering field experiment?. Issue 8 (24th August 2016) - Bast, A.; Wilcke, W.; Graf, F.; Lüscher, P.; Gärtner, H.
Abstract: Steep vegetation‐free talus slopes in high mountain environments are prone to superficial slope failures and surface erosion. Eco‐engineering measures can reduce slope instabilities and thus contribute to risk mitigation. In a field experiment, we established mycorrhizal and nonmycorrhizal research plots and determined their biophysical contribution to small‐scale soil fixation. Mycorrhizal inoculation impact on plant survival, aggregate stability, and fine root development was analyzed. Here we present plant survival ( n total  = 1248) and soil core ( n total  = 108) analyses of three consecutive years in the Swiss Alps. Soil cores were assayed for their aggregate stability coefficient (ASC), root length density (RLD), and mean root diameter (MRD). Inoculation improved plant survival significantly, but it delayed aggregate stabilization relative to the noninoculated site. Higher aggregate stability occurred only after three growing seasons. Then also RLD tended to be higher and MRD increased significantly at the mycorrhizal treated site. There was a positive correlation between RLD, ASC, and roots <0.5 mm, which had the strongest impact on soil aggregation. Our results revealed a temporal offset between inoculation effects tested in laboratory and field experiments. Consequently, we recommend to establish an intermediate to long‐term field experimental monitoring before transferring laboratory results to the field. Key Points: Inoculation improved plant survival and altered root growth but delayed soil stabilization A temporal offset is detected between inoculation effects tested in glasshouse studies and field experiments Field experiments including continuous monitoring are needed to understand the plant‐soil interactions in steep, coarse‐grained environments